Preparation method of in-situ interface residual alkali conversion stable secondary battery positive electrode material
The surface residual alkali of the layered oxide positive electrode material is transformed by inorganic fluoride and organic solvent treatment, forming a polymer coating, solving the problem of interface instability of the positive electrode material and significantly improving its circulation performance and air stability.
Patent Information
- Application Number
- CN202510031990.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
In practical applications, layered oxide positive electrode materials have degraded performance due to surface residual alkali and interface instability, which limits their application.
Through inorganic fluoride and organic solvent treatment, the residual alkali on the surface is converted in situ to form a heteroepitaxial ion conductor organic polymer coating to enhance electron and ion transport at the interface of the positive electrode material.
The reduction of residual alkali on the surface of the positive electrode material is achieved, the interface stability and circulation performance are enhanced, and more stable capacity output and excellent air stability are shown.
Smart Images

Figure CN119430315A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy materials and secondary batteries, and particularly relates to a method for preparing a secondary battery positive electrode material by in-situ interface residual alkali conversion stabilization. Background Art
[0002] In the field of secondary batteries, lithium-ion batteries dominate due to their high energy density and long life. With the continuous development of technology, sodium-ion batteries have gradually shown their unique competitiveness in the field of secondary batteries due to their cost advantages and safety, and together with lithium-ion batteries, they have promoted the development and application of secondary battery technology.
[0003] Among the cathode materials for lithium-ion batteries and sodium-ion batteries, layered oxides have become attractive cathode candidates for rechargeable secondary batteries due to their high theoretical capacity. During transportation and electrode preparation, a variety of alkaline substances, such as hydroxides and carbonates, will be produced and accumulated on the surface of layered oxide cathode materials, which will cause problems such as gelation of cathode material slurry, corrosion of current collectors, poor mechanical properties, battery gas production, and degradation of electrical performance, limiting their practical applications. Among them, constructing surface coatings (such as metal oxides, fluorides, phosphates, and spinel oxides) is a common strategy to solve the physical and chemical problems of layered oxide cathode materials.
[0004] In existing technologies, metal oxides (Al2O3, TiO2, and MgO) and fluorides (LiF, AlF3) as inert coating materials can improve the cycling performance by reducing surface side reactions, while their poor ion transport ability will hinder the Li + 、Na + In addition, metal phosphates (Li3PO4, AlPO4) have excellent ionic conductivity, but poor electronic conductivity and structural stability; spinel oxides have a three-dimensional skeleton and have a good lattice match with layered oxides, which are considered to be a stable phase surface layer, but they will sacrifice a large original capacity.
[0005] Based on this, the present invention proposes to transform the surface residual alkali in situ by treating with inorganic fluoride and organic solvent, and at the same time form a heteroepitaxial ion conductor organic polymer coating. The surface polymer coating of the positive electrode material reduces the surface residual alkali, and has versatility and effectiveness in controlling the residual alkali and enhancing the interfacial stability of the layered oxide positive electrode of the rechargeable secondary battery. The polymer coating formed by the conversion of the interface residual alkali is an ion conductor, which can enhance the electron and ion transmission at the interface of the positive electrode material, and at the same time, it exhibits a specific capacity comparable to that of the original material and a more stable capacity output during the charging and discharging process, reduces voltage hysteresis and capacity attenuation, and has excellent cycle stability and structural stability. In addition, this polymer coating does not contain hydrophilic groups, has hydrophobicity, and meets the requirements of transportation and storage in large-scale production applications. The present invention provides a solution to overcome the problems of surface residual alkali and interfacial instability of layered oxide positive electrode materials in actual production applications, and effectively promotes the practical application of positive electrode materials. Summary of the invention
[0006] In order to solve the deficiencies in the prior art, the present invention proposes a method of in-situ conversion of surface residual alkali by treating with inorganic fluoride and organic solvent, and forming a heteroepitaxial ion conductor organic polymer coating at the same time, so as to solve the surface residual alkali and interface instability problems of layered oxide positive electrode materials in practical applications. The material has the advantages of excellent interface stability and cycle performance. Another advantage of the present invention is that the synthesis process is simple and controllable, which can improve air stability and promote the practical production and application of layered oxide positive electrode materials.
[0007] The preparation method of in-situ interface residual alkali conversion stabilized secondary battery positive electrode material, the technical scheme is as follows: Preparation of S1 precursor materials: Weigh the alkali metal source and transition metal source according to the stoichiometric ratio, place them in a natural agate mortar and grind them thoroughly for 0.5-1h until they are evenly ground. Then use a tablet press and a corresponding mold (10mm in diameter) to press the mixed precursor materials into cylindrical sheets (10mm in diameter, 3-5mm in height) at a pressure of 16-20Mpa.
[0008] S2 sintering of positive electrode material: put the cylindrical slice obtained in step S1 into a corundum porcelain boat, and then place it in a muffle furnace, sinter it to 800-1100℃ in air at a heating rate of 2-5℃ / min, calcine for 10-16 hours, and naturally cool it to about 100℃. Then take out the sintered cylindrical slice, place the sintered cylindrical slice in an agate mortar, and grind it thoroughly for 10-20 minutes until it is evenly ground to obtain a powdered positive electrode material.
[0009] S3 coating treatment: the sample obtained in step S2 is mixed with a certain concentration of inorganic fluoride in an alcohol solution, and then placed on a stirrer and stirred at 300-500 rpm for 2 hours. The stirred solution is dried to finally obtain a powdered fluorinated positive electrode material. The fluorinated positive electrode material is mixed with an organic mixed solvent, and placed on a stirrer at 300-500 rpm again, stirred for 0.5-1 hour, and then dried.
[0010] S4 low-temperature calcination: Place the dried material in a corundum porcelain boat, then place it in a tubular furnace, sinter it to 200-400°C at a heating rate of 2-5°C / min in an inert gas, calcine for 2-5h, and naturally cool to around room temperature to obtain the final polymer @ layered positive electrode material.
[0011] A positive electrode material for in-situ interface residual alkali conversion, a polymer / layered structure, with a chemical expression of AM x TMO2, wherein x>0.5 is a layered oxide positive electrode material. The coating is formed by the conversion of the residual alkali at the interface and coated on the surface of the layered oxide. AM is one or more of Li and Na; the transition metal TM is one or more of Ni, Co, Mn, Fe, Cu, Zn, Cr, and Ti. The layered oxide positive electrode material coated with the polymer coating has a coating thickness of 2-10 nm, preferably 2-5 nm.
[0012] Further, the alkali metal source in step S1 is one or more of a sodium source and a lithium source, the sodium source is selected from one or more of sodium sulfate, sodium acetate, sodium formate, sodium carbonate, sodium chloride, disodium hydrogen phosphate, sodium dihydrogen phosphate, and the lithium source is selected from one or more of lithium carbonate, lithium oxalate, lithium acetate, lithium sulfate, lithium hydroxide, and lithium chloride; wherein the transition metal TM is at least one of Ni, Co, Mn, Fe, Cu, Zn, Cr, and Ti elements, and the transition metal TM source comes from one or more of the oxides, nitrates, phosphates, carbonates, oxalates, and acetates corresponding to the TM. Among them, since part of the alkali metal source will volatilize during high-temperature sintering, 3-10 wt% of the alkali metal source should be appropriately increased.
[0013] Furthermore, in step S3, the inorganic fluoride is selected from one or more of anhydrous hydrogen fluoride, ammonium fluoride, ammonium bifluoride, potassium bifluoride, sodium bifluoride, aluminum fluoride, sodium fluoride, lithium fluoride, and calcium fluoride.
[0014] Furthermore, in step S3, the organic solvent is selected from one of ether, acetone, propylene oxide, tetrahydrofuran, epichlorohydrin, ethylene oxide, and 1,2-butylene oxide, or a mixture thereof.
[0015] Furthermore, the drying method in step S3 is one or more of air drying, water bath drying, oil bath drying, rotary evaporation drying, and vacuum drying.
[0016] Furthermore, the alcohol solution in step S3 is one or more of anhydrous ethanol, methanol, and propanol.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The synthesis process of the present invention is simple and controllable, and can be applied to layered oxide positive electrode materials for lithium-ion batteries, and can also be further extended to layered oxide positive electrode materials for sodium-ion batteries, and has wide applicability.
[0018] (2) The method of the present invention converts the residual alkali on the surface in situ by treating with inorganic fluoride and organic solvent, and simultaneously forms a heteroepitaxial ion conductor organic polymer coating, which shows its versatility and effectiveness in controlling the residual alkali and enhancing the interfacial stability of the layered oxide positive electrode of rechargeable secondary batteries. In addition, the polymer coating formed by the conversion of the interfacial residual alkali enhances the electron and ion transport at the interface, while showing a more stable capacity output during the charge and discharge process, reducing voltage hysteresis and capacity decay, and having excellent cycle stability.
[0019] (3) The organic skeleton in the polymer coating converted by the interfacial residual alkali does not contain a hydrophilic group. According to the requirements for transportation and storage of the material in large-scale production applications, the present invention conducts an air exposure experiment on the material. Characterization technology and electrochemical performance testing are used to prove its excellent air stability, which is conducive to large-scale practical production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope (SEM) photograph of the positive electrode material prepared in Example 1.
[0021] Figure 2 This is a transmission electron microscope (TEM) image of the positive electrode material prepared in Example 1.
[0022] Figure 3 This is a scanning electron microscope (SEM) photograph of the positive electrode material prepared in Comparative Example 3.
[0023] Figure 4 This is a transmission electron microscope (TEM) image of the positive electrode material prepared in Comparative Example 3.
[0024] Figure 5 O 1s X-ray photoelectron spectroscopy (XPS) of the positive electrode materials prepared in Example 1 and Comparative Example 3.
[0025] Figure 6The first cycle voltage drop and coulomb efficiency diagram of the positive electrode materials prepared in Example 1 and Comparative Example 3 in the voltage range of 2.0-4.8 V and the current density of 0.1 C.
[0026] Figure 7 The rate performance of the positive electrode material prepared in Example 1 in the voltage range of 2.0-4.8 V.
[0027] Figure 8 The rate performance of the positive electrode material prepared in Comparative Example 3 in the voltage range of 2.0-4.8 V.
[0028] Fig. 9 The graphs show the cycling performance and energy density of the positive electrode materials of Example 1 and Comparative Example 3 in the voltage range of 2.0-4.8 V and the current density of 0.5 C.
[0029] Fig.10 The long cycle performance of the positive electrode materials prepared in Example 1 and Comparative Example 3 in the voltage range of 2.0-4.8 V and at a current density of 1 C.
[0030] Fig.11 This is a transmission electron microscope (TEM) image of the positive electrode material prepared in Example 2.
[0031] Fig.12 Fourier transform infrared spectra (FT-IR) of the positive electrode materials prepared in Example 2 and Comparative Example 4.
[0032] Fig.13 Comparison of pH values of the positive electrode materials prepared in Example 2 and Comparative Example 4.
[0033] Fig.14 The first cycle charge and discharge curves of the positive electrode materials prepared in Example 2 and Comparative Example 4 at a voltage range of 2.0-4.0 V and a current density of 0.1 C.
[0034] Fig.15 Comparison of the first-cycle voltage drop and coulomb efficiency of the positive electrode materials prepared in Example 2 and Comparative Example 4 in the voltage range of 2.0-4.0 V and the current density of 0.1 C.
[0035] Fig.16 The charge and discharge curves of the positive electrode materials prepared in Example 2 and Comparative Example 4 at different rates in the voltage range of 2.0-4.0 V.
[0036] Fig.17 The figure shows the comparison of the rate performance of the positive electrode materials prepared in Example 2 and Comparative Example 4 in the voltage range of 2.0-4.0 V.
[0037] Fig.18This is a comparison chart of the median voltage and energy efficiency performance of the positive electrode materials prepared in Example 2 and Comparative Example 4 in the voltage range of 2.0-4.0 V at different current densities.
[0038] Fig.19 Comparison of the long cycle performance of the positive electrode materials prepared in Example 2 and Comparative Example 4 in the voltage range of 2.0-4.0 V and at a current density of 1 C.
[0039] Fig. 20 The contact angle test results of the positive electrode materials prepared in Example 2 and Comparative Example 4.
[0040] Fig.21 Comparison of rate performance in the voltage range of 2.0-4.0 V after air exposure experiment for the positive electrode materials prepared in Example 2 and Comparative Example 4.
[0041] Fig. 22 After the positive electrode materials prepared in Example 2 and Comparative Example 4 were exposed to air, the long cycle performance was compared at a current density of 1 C in the voltage range of 2.0-4.0 V. DETAILED DESCRIPTION
[0042] The following is a further explanation of the preparation method of the in-situ interfacial residual alkali conversion stable secondary battery positive electrode material described in the present invention in conjunction with specific embodiments. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any simple modifications, equivalent changes and modifications made to the following examples based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
[0043] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0044] Example 1, 1. Preparation of polymer @Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 layered cathode material, S1, preparation of precursor materials: lithium carbonate (excess 3-10 wt%), nickel oxide, cobalt trioxide and manganese trioxide were weighed according to the stoichiometric ratio of 1.2:0.13:0.13:0.54, and ground in a natural agate mortar for 45 minutes until the grinding was uniform. Then, a tablet press and a corresponding mold (diameter of 10 mm) were used to press the mixed precursor materials into cylindrical sheets (diameter of 10 mm, height of 3-5 mm) at a pressure of 18 MPa.
[0045] S2, sintering of positive electrode materials: the cylindrical slices obtained in step S1 are placed in a corundum porcelain boat, and then placed in a muffle furnace, and sintered to 1000°C at a heating rate of 5°C / min in air, calcined for 15 hours, and naturally cooled to about 100°C. The sintered cylindrical slices can be taken out, and the sintered cylindrical slices are placed in an agate mortar and ground for 15 minutes until they are evenly ground to obtain powdered positive electrode materials.
[0046] S3, coating treatment: the sample obtained in step S2 was mixed with 3wt% inorganic fluoride in an ethanol solution, and then placed on a stirrer and stirred at 300-500rpm for 2h. The stirred solution was placed in an oil bath at 80℃ for oil bath drying, and finally a powdered fluorinated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2. Fluorinated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, and an organic mixed solvent of tetrahydrofuran: propylene oxide in a volume ratio of 3:1, and then placed on a stirrer at a speed of 300-500 rpm and stirred for 0.5-1h. The solution was then placed in a water bath at 60°C to evaporate the solvent to obtain a dry material.
[0047] S4, low-temperature calcination: The dried material is placed in a corundum porcelain boat, and then placed in a tube furnace, sintered to 300°C at a heating rate of 2-3°C / min in an inert gas, calcined for 3h, and naturally cooled to room temperature to obtain the final polymer @Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0048] 2. Battery assembly part The prepared sample, polyvinylidene fluoride (PVDF) and conductive agent (Super P) are mixed in a mass ratio of 7:2:1, N-methylpyrrolidone (NMP) is used as the solvent, placed in an oscillation tube, and oscillated by an oscillator for 30 minutes to prepare a uniform slurry. Subsequently, the slurry is evenly coated on the aluminum foil current collector, and then placed in a vacuum drying oven at 80°C and vacuum dried for 12 hours. The positive electrode sheet can be taken out after the vacuum oven cools to room temperature. The positive electrode sheet is cut into positive electrode discs with a diameter of 12 mm using a cutting machine, and the positive electrode active material loading of the disc is 1-1.2 mg / cm -2, stored in a glove box with argon atmosphere for later use. The above-mentioned positive electrode sheet, lithium metal as the negative electrode material, Whatman glass fiber membrane as the separator, 1 mol / L NaClO4 (the solvent is a mixture of ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 and 5% fluoroethylene carbonate) as the electrolyte, are assembled into a button half-cell in an argon-protected glove box. After adding 100-120 microliters of electrolyte, the battery is packaged and the electrical performance is tested at room temperature. The voltage range of the battery test is 2.0-4.8 V.
[0049] Example 2, 1. Preparation of polymer @NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered cathode material, S1, preparation of precursor materials: Sodium carbonate (excess 3-10 wt%), nickel oxide, iron oxide and manganese trioxide were weighed according to the stoichiometric ratio of 1:1 / 3:1 / 3:1 / 3, and ground in a natural agate mortar for 45 min until the grinding was uniform. Then, a tablet press and a corresponding mold (diameter of 10 mm) were used to press the mixed precursor materials into cylindrical sheets (diameter of 10 mm, height of 3-5 mm) at a pressure of 18 MPa.
[0050] S2, sintering of positive electrode materials: the cylindrical slices obtained in step S1 are placed in a corundum porcelain boat, and then placed in a muffle furnace, and sintered to 1000°C at a heating rate of 5°C / min in air, calcined for 15 hours, and naturally cooled to about 100°C. The sintered cylindrical slices can be taken out, and the sintered cylindrical slices are placed in an agate mortar and ground for 15 minutes until they are evenly ground to obtain powdered positive electrode materials.
[0051] S3, coating treatment: the sample obtained in step S2 was mixed with 3wt% inorganic fluoride in an ethanol solution, and then placed on a stirrer and stirred at 300-500rpm for 2h. The stirred solution was placed in an oil bath at 80℃ for oil bath drying, and finally a powdered fluorinated NaNi was obtained. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2. Fluorinated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, and an organic mixed solvent of tetrahydrofuran: propylene oxide in a volume ratio of 3:1, and then placed on a stirrer at a speed of 300-500 rpm and stirred for 0.5-1h. The solution was then placed in a water bath at 60°C to evaporate the solvent to obtain a dry material.
[0052] S4, low-temperature calcination: The dried material is placed in a corundum porcelain boat, and then placed in a tube furnace, sintered to 300°C at a heating rate of 2-3°C / min in an inert gas, calcined for 3h, and naturally cooled to room temperature to obtain the final polymer @NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0053] 2. Battery assembly part The button half-cell assembly was performed in the same manner as in Example 1. Sodium metal was used as the negative electrode material. The voltage range of the battery test was 2.0-4.0 V.
[0054] Example 3 The experimental steps and battery assembly are the same as those in Example 1, except that the proportion of NH4F is changed to 4 wt%.
[0055] In Example 4, the experimental steps and battery assembly are the same as those in Example 2, except that the proportion of NH4F is changed to 4wt%.
[0056] Example 5 The experimental steps and battery assembly are the same as those in Example 1, except that the proportion of NH4F is changed to 5wt%.
[0057] Example 6, the experimental steps and battery assembly are the same as those of Example 2, except that the proportion of NH4F is changed to 5wt%.
[0058] Example 7 The experimental steps and battery assembly are the same as those in Example 1, except that 3 wt % NH4F is replaced by 3 wt % ammonium bifluoride.
[0059] In Example 8, the experimental steps and battery assembly are the same as those in Example 2, except that 3 wt % NH 4 F is replaced by 3 wt % ammonium bifluoride.
[0060] Example 9 The experimental steps and battery assembly are the same as those in Example 1, except that 3 wt % NH4F is replaced by 3 wt % aluminum fluoride.
[0061] In Example 10, the experimental steps and battery assembly are the same as those in Example 2, except that 3 wt % NH4F is replaced by 3 wt % aluminum fluoride.
[0062] Embodiment 11 The experimental steps and battery assembly were the same as those in Example 1, except that the volume ratio of tetrahydrofuran:propylene oxide was changed to 4:1.
[0063] In Example 12, the experimental steps and battery assembly are the same as those in Example 2, except that the volume ratio of tetrahydrofuran:propylene oxide is changed to 4:1.
[0064] Embodiment 13 The experimental steps and battery assembly were the same as those in Example 1, except that the volume ratio of tetrahydrofuran to propylene oxide was changed to 5:1.
[0065] In Example 14, the experimental steps and battery assembly are the same as those in Example 2, except that the volume ratio of tetrahydrofuran:propylene oxide is changed to 5:1.
[0066] Embodiment 15 The experimental steps and battery assembly are the same as those in Example 1, except that the organic solvent is changed to ether:propylene oxide = 3:1.
[0067] In Example 16, the experimental steps and battery assembly are the same as those in Example 2, except that the organic solvent is changed to ether: propylene oxide = 3:1.
[0068] Embodiment 17 The experimental steps and battery assembly are the same as those in Example 1, except that the organic solvent is changed to acetone:propylene oxide = 3:1.
[0069] In Example 18, the experimental steps and battery assembly are the same as those in Example 2, except that the organic solvent is changed to acetone:propylene oxide = 3:1.
[0070] Embodiment 19 The experimental steps and battery assembly are the same as those in Example 1, except that the organic solvent is changed to tetrahydrofuran:ethylene oxide = 3:1.
[0071] In Example 20, the experimental steps and battery assembly are the same as those in Example 2, except that the organic solvent is changed to tetrahydrofuran:ethylene oxide = 3:1.
[0072] Embodiment 21 The experimental steps and battery assembly are the same as those in Example 1, except that the organic solvent is changed to tetrahydrofuran:epichlorohydrin=3:1.
[0073] In Example 22, the experimental steps and battery assembly are the same as those in Example 2, except that the organic solvent is changed to tetrahydrofuran:epichlorohydrin = 3:1.
[0074] Embodiment 23 The experimental steps and battery assembly are the same as those in Example 1, except that the organic solvent is changed to tetrahydrofuran:1,2-butylene oxide=3:1.
[0075] In Example 24, the experimental steps and battery assembly are the same as those in Example 2, except that the organic solvent is changed to tetrahydrofuran:1,2-butylene oxide=3:1.
[0076] Comparative Example 1 The experimental steps and battery assembly are the same as those in Example 1, except that in step (S3): the sample obtained in step (S2) is mixed with 3wt% NH4F in an ethanol solution, and then placed on a stirrer and stirred at 300-500 rpm for 2 hours. The stirred solution is placed in an oil bath at 80°C for oil bath drying, and finally a powdered fluorinated Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0077] Comparative Example 2, the experimental steps and battery assembly are the same as those of Example 2, except that in step (S3): the sample obtained in step (S2) is mixed with 3wt% NH4F in an ethanol solution, then placed on a stirrer and stirred at 300-500 rpm for 2 hours. The stirred solution is placed in an oil bath at 80°C for oil bath drying, and finally a powdered fluorinated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.
[0078] Comparative Example 3 1. Preparation of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 layered cathode material, Preparation of S1 precursor materials: lithium carbonate (3-10 wt% excess), nickel oxide, cobalt trioxide and manganese trioxide were weighed according to the stoichiometric ratio of 1.2:0.13:0.13:0.54, and ground in a natural agate mortar for 45 minutes until the grinding was uniform. Then, a tablet press and a corresponding mold (10 mm in diameter) were used to press the mixed precursor materials into cylindrical sheets (10 mm in diameter and 3-5 mm in height) at a pressure of 18 MPa.
[0079] S2 sintering of positive electrode materials: put the cylindrical slices obtained in step S1 into a corundum porcelain boat, and then place it in a muffle furnace, sinter it to 1000°C in air at a heating rate of 5°C / min, calcine for 15 hours, and naturally cool it to about 100°C. Then take out the sintered cylindrical slices, place the sintered cylindrical slices in an agate mortar, and grind them thoroughly for 15 minutes until they are evenly ground to obtain powdered positive electrode materials.
[0080] 2. Battery assembly The battery assembly is the same as in Example 1.
[0081] Comparative Example 4, 1. Preparation of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered cathode material (S1) Preparation of precursor materials: Sodium carbonate (excess 3-10 wt%), nickel oxide, iron oxide and manganese trioxide were weighed according to the stoichiometric ratio of 1:1 / 3:1 / 3:1 / 3, and ground in a natural agate mortar for 45 min until the grinding was uniform. Then, a tablet press and a corresponding mold (diameter 10 mm) were used to press the mixed precursor materials into cylindrical sheets (diameter 10 mm, height 3-5 mm) at a pressure of 18 MPa.
[0082] (S2) Sintering of positive electrode materials: The cylindrical slices obtained in step S1 are placed in a corundum porcelain boat, and then placed in a muffle furnace. They are sintered to 1000°C at a heating rate of 5°C / min in air, calcined for 15 hours, and naturally cooled to about 100°C. The sintered cylindrical slices can be taken out, placed in an agate mortar, and ground for 15 minutes until they are evenly ground to obtain powdered positive electrode materials.
[0083] 2. Battery assembly The battery assembly is the same as in Example 2. The electrochemical performance test results are shown in Table 1.
[0084] Table 1 Electrical properties of prepared cathode materials
[0085] The process provided by the present invention utilizes the reaction of inorganic fluoride with residual alkaline compounds on the surface, and further treats with an organic solvent for polymerization reaction, so as to realize the in-situ conversion of residual alkali on the surface into a polymer coating, thereby preparing a high-performance layered oxide positive electrode material. Table 1 compares the first cycle charge specific capacity at 0.1C, the first cycle discharge specific capacity, and the capacity retention rate after 100 cycles at a rate of 1C for the layered oxide positive electrode material prepared by the present invention.
[0086] Based on these results, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) tests were performed on Example 1 and Comparative Example 3 to obtain detailed information about their morphological and structural characteristics. Figure 1 ) and Comparative Example 3 ( Figure 3 ) showed that the sample consisted of spherical secondary particles with a size of about 10 µm, which were aggregated from subnanometer primary particles, and the interface treatment did not destroy this spherical morphology. Figure 4TEM shows that the surface of Comparative Example 3 has irregular impurities, mainly composed of amorphous LiOH and Li2CO3. Figure 2 Example 1 exhibits a smooth, flat surface with a uniform, thin coating, which may be due to the effective removal of residual alkaline compounds on the surface during the interface treatment and subsequent surface reconstruction. At the same time, a uniform amorphous heteroepitaxial polymer coating with a thickness of about 5 nm can be observed. The surface chemical properties of Example 1 and Comparative Example 3 were analyzed using X-ray photoelectron spectroscopy (XPS). Example 1 ( Figure 5 a) and Comparative Example 3 ( Figure 5 b) The O 1s XPS spectrum shows peaks at 529.4 eV, 531.6 eV, and 533.9 eV, corresponding to lattice oxygen, OH − and oxygen in carbonates. In Example 1, OH − The peak intensity of the carbonate oxygen was significantly reduced, indicating that the residual alkaline substances were significantly reduced. The organic polymer coating has no hydrophilic groups and has hydrophobic properties, which can inhibit the adsorption of water and hydroxyl groups and reduce the surface OH − and CO3 2− . Figure 6-10 The electrochemical tests show that the performance of Example 1 is significantly better than that of Comparative Example 3. These results show that Example 1 after interface treatment has significant advantages in cycle stability, specific capacity and rate performance. Fig.11 The TEM image of Example 2 confirms the presence of the polymer coating. Fig.12 The infrared spectrum (FT-IR) in the experiment shows that Example 2 has a characteristic peak at 2362 cm⁻¹, which is attributed to the stretching vibration of the CH bond, while this peak is not detected in Comparative Example 4. In addition, the Example 2 sample shows a peak of HCO3⁻ at 1155 cm⁻¹, while 1429 cm⁻¹ and 883 cm⁻¹ correspond to CO3 2⁻ The signal weakened, indicating that the residual alkali on the surface decreased and a polymer coating was formed. Fig.13 As shown, the pH value measured in Example 2 is 13.542, which is lower than the pH value 14.014 of Comparative Example 4. Fig.14 Example 2 and Fig. 22 From the SEM images of Comparative Example 4, both samples are composed of irregular micron-sized plate-like particles, with no significant difference. Figure 14-22 ), indicating that the performance of Example 2 is significantly better than that of Comparative Example 4. Based on these results, our strategy solves the problems of poor air stability, poor ion transport, and interface side reactions by implementing interface treatment to remove surface residual alkali and simultaneously constructing a polymer coating, while showing strong versatility and universality, and is suitable for actual production applications of secondary battery systems.
Claims
1. A method for preparing a secondary battery positive electrode material by in-situ interface residual alkali conversion stabilization, characterized in that: The following steps are involved: S1, preparation of precursor materials: weigh the alkali metal source and the transition metal source according to the stoichiometric ratio, place them in an agate mortar and grind them thoroughly for 0.5-1h until they are evenly ground; then use a tablet press and a corresponding mold with a diameter of 10mm and a pressure of 16-20Mpa to press the mixed precursor materials into cylindrical sheets with a diameter of 10mm and a height of 3-5mm; S2, sintering of positive electrode material: placing the cylindrical slice obtained in step S1 into a corundum porcelain boat, and then placing it in a muffle furnace, sintering it to 800-1100°C at a heating rate of 2-5°C / min in air, calcining for 10-16h, and naturally cooling it to about 100°C, then taking out the sintered cylindrical slice, placing the sintered cylindrical slice in an agate mortar, and grinding it thoroughly for 10-20min until it is evenly ground, thereby obtaining a powdered positive electrode material; S3, coating treatment: the sample obtained in step S2 is mixed with an inorganic fluoride in an alcohol solution, and then placed on a stirrer, stirred at a speed of 300-500 rpm for 2 hours, and the stirred solution is dried to finally obtain a powdered fluorinated sample material, and the fluorinated sample material is mixed with an organic solvent, and placed on a stirrer at a speed of 300-500 rpm again, stirred for 0.5-1 hour, and then dried; S4, low-temperature calcination: the dried material is placed in a corundum porcelain boat, and then placed in a tube furnace, sintered to 200-400°C at a heating rate of 2-5°C / min in an inert gas, calcined for 2-5h, and naturally cooled to room temperature to obtain the final polymer @ layered cathode material; The layered oxide cathode material converted from in-situ interfacial residual alkali is a polymer / layered structure with the chemical expression AM x TMO2, wherein x>0.5 is a layered oxide positive electrode material; AM is one or more of Li and Na; TM is at least one of the transition metal elements Ni, Co, Mn, Fe, Cu, Zn, Cr, and Ti; the coating is a polymer formed by the conversion of interfacial residual alkali and coated on the surface of the layered oxide, and the coating thickness is 2-10nm.
2. The method for preparing a secondary battery positive electrode material by in-situ interfacial residual alkali conversion stabilization according to claim 1, characterized in that: In step S1, the alkali metal source is one or more of sodium salt and lithium salt; TM is selected from one or more of corresponding oxides, nitrates, phosphates, carbonates, oxalates and acetates.
3. The method for preparing a secondary battery positive electrode material by in-situ interfacial residual alkali conversion stabilization according to claim 1, characterized in that: The inorganic fluoride in step S3 is selected from one or more of anhydrous hydrogen fluoride, ammonium fluoride, ammonium bifluoride, potassium bifluoride, sodium bifluoride, aluminum fluoride, sodium fluoride, lithium fluoride, and calcium fluoride.
4. The method for preparing a secondary battery positive electrode material by in-situ interfacial residual alkali conversion stabilization according to claim 1, characterized in that: The organic solvent in step S3 is selected from one or more of diethyl ether, acetone, propylene oxide, tetrahydrofuran, epichlorohydrin, ethylene oxide, and 1,2-butylene oxide.
5. The method for preparing a secondary battery positive electrode material by in-situ interfacial residual alkali conversion stabilization according to claim 1, characterized in that: The drying method in step S3 is one or more of air drying, water bath drying, oil bath drying, rotary evaporation drying, and vacuum drying.
6. The method for preparing a secondary battery positive electrode material by in-situ interfacial residual alkali conversion stabilization according to claim 1, characterized in that: The alcohol solution in step S3 is one or more of anhydrous ethanol, methanol, and propanol.
7. A secondary battery, characterized in that: The raw material for preparing the positive electrode includes the positive electrode material obtained by any preparation method in claims 1-6.
Citation Information
Patent Citations
Sodium-ion battery layered positive electrode material coated with oxyfluoride in situ and preparation method of sodium-ion battery layered positive electrode material
CN114678509A
Sodium-ion battery positive electrode material, preparation method thereof, sodium-ion battery positive electrode plate and sodium-ion battery
CN115763717A
Ternary positive electrode material, preparation method and application thereof
CN115939367A
Preparation method of long-circulation sodium ion battery positive electrode material and sodium ion battery
CN116895744A
Polymer-coated high-nickel positive electrode material and preparation method thereof
CN118231624A
Cited By
Composite coated nickel cobalt lithium aluminate positive electrode material as well as preparation method and application thereof
CN120573766A
Preparation method of composite solid electrolyte coated modified positive electrode material
CN120834207A